ANALISIS PENGARUH GAYA KEPEMIMPINAN TERHADAP KEDISIPLINAN PEGAWAI PADA KANTOR SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) KOTA BIMA - Jaenab Jaenab; Firman kusumayadi (Jurnal Akrab Juara, 2018)
The purpose of the study is to determine whether the leadership style has a positive and significant effect on the discipline of employee work on One Roof Management System (Samsat) of Bima Town. The type of this research is associated research. The collect of the research data by using the spreading of cueisioner with a sample of 36 employees with the technique of data analysis using simple linear regression. The result of this study is T value = 1.085 and t table = 2,041, so t calculate smaller than t table (1.085 <2.041) hence it is stated that t hitung falls on acceptance area Ho means there is no relationship of leadership style to employee Dept. One Roof Management One (Samsat) of Bima Town or Ho is accepted and Ha is rejected. Keywords: Leadership style, employee discipline.